2011
DOI: 10.1186/1471-2458-11-246
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of healthcare professionals' intention and behaviour to encourage physical activity in patients with cardiovascular risk factors

Abstract: BackgroundHealthcare professionals can play a crucial role in optimizing the health status of patients with cardiovascular risk factors (abdominal obesity, high blood pressure, low HDL cholesterol, elevated triglycerides and elevated blood glucose). In order to do this, it is imperative that we understand the social-cognitive determinants (including habits) that underlie healthcare professionals' intention and the corresponding behavior of actually encouraging patients with cardiovascular risk factors to engag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 45 publications
1
40
0
Order By: Relevance
“…We undertook a separate planning process for health professionals because they perform different behaviors with different social-cognitive determinants related to the intention and behavior in question than their patients with cardiovascular risk factors do [18,19]. Within each step of the Intervention Mapping protocol, the application for health professionals is presented followed by the application for patients with cardiovascular risk factors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We undertook a separate planning process for health professionals because they perform different behaviors with different social-cognitive determinants related to the intention and behavior in question than their patients with cardiovascular risk factors do [18,19]. Within each step of the Intervention Mapping protocol, the application for health professionals is presented followed by the application for patients with cardiovascular risk factors.…”
Section: Resultsmentioning
confidence: 99%
“…Focus group interviews with health professionals (n = 7) revealed that encouraging patients to become physically active was seen as an integral part of their daily practice and, although perceived as relatively easy to do, patient compliance was often a problem. In previous research, we studied through questionnaire the social-cognitive determinants of intention and behavior to encourage patients with cardiovascular risk factors to become physically active [19-28]. Input for the Intervention Mapping process showed that health professionals’ encouragement of physical activity among cardiovascular patients could be predicted by high levels of intention to encourage physical activity among these patients [19].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the review by Thompson‐Leduc et al () on studies about SDM behaviour explained by the TPB, the predictability of the variance of intention varied, with R 2 values ranging from 15% to 88%. Other mentioned factors explaining intention for SDM behaviour are self‐efficacy (Foy et al, ; Ten Wolde, Dijkstra, Empelen, Knuistingh Neven, & Zitman, ) and moral and professional norms (Daneault, Beaudry, & Godin, ; Godin et al, ; Sassen, Kok, & Vanhees, ; Thompson‐Leduc et al, ). In our study, the strongest predictor for SDM intention was perceived behavioural control, a finding which is not in line with the review by Thomas Leduc et al ().…”
Section: Discussionmentioning
confidence: 99%
“…This finding was significant because peers not only influence behaviour but also the uptake of new programs at both individual and group levels (Harvey & Kitson, 2015). The expectations of peers and the perception that others are engaged in a behaviour strengthen intention and are therefore needed when introducing an intervention (Sassen, Kok, & Vanhees, 2011). Kortteisto et al (2010) found that nurses who sensed social pressure had stronger intention towards using clinical practice guidelines than those who did not perceive social pressure.…”
Section: Discussionmentioning
confidence: 99%